2014
DOI: 10.3233/jrs-140623
|View full text |Cite
|
Sign up to set email alerts
|

Medication safety strategies in hospitals – A systematic review

Abstract: BACKGROUND: Medication safety is an essential component of patient safety in health care delivery. Providing strategies to effectively prevent medication errors and adverse drug events in hospitals has gained international recognition. OBJECTIVE: The aim of this paper was to review systematically the research literature on the various interventions for providing medication safety in hospitals. METHOD: Eight healthcare databases were searched for full research articles written in English. Reference lists of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 56 publications
0
66
0
Order By: Relevance
“…Some studies indicate that these interventions improve patient management or clinically relevant outcomes [20]. However, most studies were methodologically weak, as they used non-blinded designs and lacked robust data collection methods [16,[38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that these interventions improve patient management or clinically relevant outcomes [20]. However, most studies were methodologically weak, as they used non-blinded designs and lacked robust data collection methods [16,[38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…From these 19 systematic reviews, three (Kuo 2006, Pepper & Towsley 2007, Voshall et al 2013) were found to be methodologically weak (AMSTAR < 5) and were subsequently excluded. A total of 16 reviews ranging from high to medium quality were eligible for inclusion, including four each from Australia (Hodgkinson et al 2006, Manias et al 2012, 2014, Raban & Westbrook 2014; and the United Kingdom (Conroy et al 2007, Wimpenny & Kirkpatrick 2010, Alsulami et al 2012, Keers et al 2014; two each from the United States (Gonzales 2010, Ohashi et al 2014; and Netherlands (D€ uckers et al 2009(D€ uckers et al , Maaskant et al 2015; and one each from Canada (Wulff et al 2011); Germany (Hopkinson & Jennings 2013); Ghana (Acheampong et al 2014) and Sweden (Kullberg et al 2013). These medication safety reviews focused on aged care settings, and adult and paediatric acute care settings.…”
Section: Search Strategymentioning
confidence: 99%
“…Education and training are widely used as an approach to improve nurses' medication practices, particularly regarding pharmacology and medication calculations. We identified seven reviews (Hodgkinson et al 2006, Conroy et al 2007, D€ uckers et al 2009, Manias et al 2012, Kullberg et al 2013, Acheampong et al 2014, Keers et al 2014 that examined the effectiveness of a range of education and training programmes delivered as a stand-alone strategy. Mixed results were demonstrated in studies involving didactic education and training delivered through a range of methods such as lectures, web-based educational tools or interactive CD-ROM education programs.…”
Section: Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite identification errors being conventionally related to quality issues in blood transfusion (10) and drug administration practices (11), diagnostics is not seen as a safer arena, inasmuch as misidentification is an important source of both medical imaging (12), pathology (13) and laboratory (14) errors. As specifically regards laboratory diagnostics, although the identification error rate typically ranges between 1–2% of all mistakes throughout the total testing process (15), the frequency has been reported to be as high as 9% in urgent testing (16).…”
Section: Introductionmentioning
confidence: 99%